Cyclic use of groundwater: An innovative way to improve performance of a groundwater source heat pump system during a cooling period. (1st July 2022) - Zhou, Meili; Cai, Fei; Arai, Komei
Abstract: The building sector is a large user of energy and thus a large emitter of CO2 . Replacing traditional energy with renewable energy in buildings can effectively reduce greenhouse gas emissions and global warming effects. This paper introduces a new groundwater source heat pump (GWSHP) system installed for air-conditioning of an official room. The main innovation of the new GWSHP system is the cyclic use of groundwater to save the electricity consumption of the lifting pump that pumps the groundwater from a well and also to reduce the amount of groundwater needed by the GWSHP system. The cyclic use of groundwater was realized by adding a circulating pump and a tank in the GWSHP system and intermittently running the lifting pump according to the water temperature in a groundwater heat exchanger. The performances of the new GWSHP system for four different operation modes of the lifting pump were evaluated and compared based on measurements of representative days in 2017 and 2019. The results show that the cyclic use of groundwater with an optimal operation mode can not only effectively improve the performance of the GWSHP system but also significantly reduce groundwater consumption. Specifically, the coefficient of performance of the GWSHP system was increased from 3.6 for conventional operation mode with no cyclic use of groundwater to 4.3 for the optimal operation mode, and the groundwater consumption per working day was significantly decreased from 9.2 m 3 for conventional operation mode to 4.0 m 3 for the optimal operation mode. Moreover, the long-term performance for three consecutive years from 2018 to 2020 was also evaluated based on measurements, and the results show that the long-term performance is almost the same as the performance of the representative day, which means that the representative day method used in this paper to evaluate the performance of the GWSHP system is feasible and reliable. The operating experience of this study can provide an important reference for the design and selection of GWSHP systems in areas with a different abundance of groundwater. Highlights: Cyclic use of groundwater can effectively improve the SCOP of the GWSHP system. Cyclic use of groundwater saved the electricity consumption of the lifting pump. Cyclic use of groundwater reduced the amount of groundwater needed by the GWSHP. Performance of the GWSHP system can be evaluated using representative day method. The new GWSHP system can be also used in areas with less groundwater resources.